2021
DOI: 10.1038/s41390-021-01584-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia is not therapeutic in a neonatal piglet model of inflammation-sensitized hypoxia–ischemia

Abstract: Background Perinatal inflammation combined with hypoxia–ischemia (HI) exacerbates injury in the developing brain. Therapeutic hypothermia (HT) is standard care for neonatal encephalopathy; however, its benefit in inflammation-sensitized HI (IS-HI) is unknown. Methods Twelve newborn piglets received a 2 µg/kg bolus and 1 µg/kg/h infusion over 52 h of Escherichia coli lipopolysaccharide (LPS). HI was induced 4 h after LPS bolus. After HI, piglets were random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 83 publications
4
36
1
Order By: Relevance
“…Part of the lack of complete neuroprotection by TH may be due to heterogeneous etiologies of injury in the clinical setting, including HIE complicated by infection or chronic placental insufficiency [38,39]. In particular, TH has not been neuroprotective in preclinical models of HI sensitized with LPS [13,40,41]. The lack of significant neuroprotection conferred by TH in our ferret model is therefore not unexpected due to the use of LPS for inflammatory presensitization, though TH animals did demonstrate improved behavioral outcomes in some tests compared to other HIH-exposed animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of the lack of complete neuroprotection by TH may be due to heterogeneous etiologies of injury in the clinical setting, including HIE complicated by infection or chronic placental insufficiency [38,39]. In particular, TH has not been neuroprotective in preclinical models of HI sensitized with LPS [13,40,41]. The lack of significant neuroprotection conferred by TH in our ferret model is therefore not unexpected due to the use of LPS for inflammatory presensitization, though TH animals did demonstrate improved behavioral outcomes in some tests compared to other HIH-exposed animals.…”
Section: Discussionmentioning
confidence: 99%
“…Examining the mechanisms of Epo neuroprotection in this model are beyond the scope of this manuscript but will form the basis of future work. By comparison, although we have not studied response to these therapies without the presensitizing effect of LPS in the model, it is likely that the inclusion of LPS is the primary reason for a lack of neuroprotective effect of TH [13,40,41]. However, as more definitive evidence is accumulating regarding the lack of TH neuroprotection in lower income settings [5], perhaps due to more protracted or chronic perinatal insults, the model as used here may be particularly useful for examining therapies for use in scenarios where TH is not beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some researchers proposed infection was the main cause of encephalopathy in African settings. More recent data from Africa [13,21] and South Asia suggest that the incidence of coexistent sepsis in Africa and South Asia is not higher than high-income countries [14] and coexistent sepsis cannot explain lack of hypothermic neuroprotection in LMIC.…”
Section: Ignoring Population Differences and Misleading Infection-ischemia Theorymentioning
confidence: 96%
“…Several animal studies have found that endotoxin-induced inflammation prior to hypoxia-ischemia severely exacerbates brain injury in newborns ( 24 31 ). In addition to the possible aggravation of brain damage, both animal ( 32 37 ) and clinical studies ( 38 41 ) have suggested that infections may affect both the efficacy and safety of therapeutic hypothermia.…”
Section: Introductionmentioning
confidence: 99%